Powinności w perspektywie kategorii znikomej społecznej szkodliwości czynu. Ujęcie praktyczne - Karsznicki, Krzysztof (Kwartalnik Prawa Publicznego, 2016)
Negligible social harmfulness of an act gives an opportunity to close an investigation as such act is not regarded as a crime. Polish Criminal Code includes factors which should be taken into consideration by a prosecutor or a judge in order to indicate the level of social harmfulness of an act. The paper presents some remarks regarding the concept of a legally binding definition of an negligible social harmfulness of an act. Author opposes the aforementioned solution. In his opinion, a prosecutor should not be bound by a legal definition of the term.